Potensi Antioksidan, Skrining, dan Identifikasi Metabolit Sekunder Ekstrak Beras Hitam (Oryza sativa L. Indica) - Fri Rahmawati; Maria Bintang; Albert Jackson Yang; Ni Made Devi Damayanti (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Black rice (Oryza sativa L. indica) is a variety of pigmented rice that, apart from acting as a popular food ingredient, can also be used for health because it has active compounds that have the potential to act as antioxidants. The research carried out aimed to determine antioxidant potency, conduct secondary metabolite screening, and characterize the active compound content of black rice extract. It was macerated using a 96% pro-analysis (p.a.) ethanol solvent. Antioxidant potency was tested using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) methods, secondary metabolite screening using the Harbone method, and identification of active compounds using Gas Chromatography-Mass Spectrometry (GC-MS). It was found that black rice extract has potential as an antioxidant, using the DPPH method, the 50% Inhibition Concentration (IC50) value of black rice extract and vitamin C was 97.34 ppm and 2.64 ppm, respectively, but using the FRAP method, the IC50 values of black rice extract and vitamin C were 181.83 ppm and 7.84 ppm, respectively. Secondary metabolite screening detected that in black rice extract there were active compounds in the flavonoid and steroid groups, GC-MS identification results showed that the extract contained the most compound, hexadecanoic acid.